GAS-LIQUID CHROMATOGRAPHY METHOD FOR SEPARATION OF MONO-ATOMIC ALYPHATIC (C1-C9) ALCOHOLS’ MIXTURE AND THEIR QUANTITATIVE ANALYSIS (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
A method for chromatographic separation and quantitative determination of mixture of nine alyphatic mono-atomic alcohols for educational purposes corresponding to the "Methods of chromatographic analysis" program for university chemical departments has been elaborated. The analysis has been carried out on LXM-72 chromatograph with flameionization detector and temperature programming. The conditions and regime of chromatography process have been justified. Duration of analyses is 25 min. Volume of analysing sample is 1 mkL.